A Reliable HPLC-ELSD Method for Determination of Cholesterol, Phosphatidylcholine, Lysophosphatidylcholine Content and the Stability of a Liposomal Formulation - de Magalhães Benedetti, Naiara I. G.; Costa Veloso, Danillo Fabrini Maciel; Nascimento, Thais L.; Almeida Diniz, Danielle Guimarães; Maione-Silva, Lorena; Lima, Eliana Martins (Current Pharmaceutical Analysis, 2020)
Background: Liposomes continue to play an important role in drug delivery research due to their ability to improve transport and targeting of a wide range of active molecules. Analysis of liposomal components is a key point in the characterization and evaluation of formulation stability. The aim of this work was to develop and validate an HPLC-ELSD method for the characterization and quality control of liposomes. Methods: HPLC-ELSD method was validated by assessing selectivity, linearity, precision, accuracy, limit of detection and quantitation. The mobile phase consisted of a 0.1% (v/v) of trifluoroacetic acid (TFA) and methanol in gradient elution. Initial rate was 20:80 (0.1% TFA: methanol), with a ramp reaching 100% methanol. HPLC-MS/MS was used to confirm the presence of the fatty acid mixture in the analyzed lipids, as well as sub-products generated under pre-determined conditions in the stability study. Results: A HPLC-ELSD method has been developed to detect and measure cholesterol, phosphatidylcholine and lysophosphatidylcholine. High specificity, sensitivity and linearity within the predetermined range for all the compounds analyzed (R2>0.99) were obtained. Accuracy and precision results for all the compounds were within the acceptance limit of ≤5% and 90-110%, respectively. Mass spectrometry results showed complementary information about the phospholipid composition to evaluate the degree of degradation of liposomes over different storage conditions. Conclusion: The method was successfully applied as a quality control tool for the analysis of a wide range of lipids, present in liposomal formulations. HPLC-MS/MS was used to ensure complete elucidation of the lipid components and the detected lyso-forms.
Keywords: LC-MS/MS